Potential of some green manure cover crops for conservation and recuperation of tropical soils - Alvarenga, Ramon Costa; da Costa, Liovando Marciano; Filho, Waldemar Moura; Regazzi, Adair José (Pesquisa Agropecuaria Brasileira, 1995)
The crops of cowpea (Vigna unguiculata), crotalaria (Crotalaria juncea and Crotalaria paulina), pigeon pea (Cajanus cajan), feijão-bravo-do-ceará (Canavalia brasiliensis), jackbean (Canavalia ensiformis), lab-lab (Dolichos lab lab), and mucuna-preta (Stizolobium aterrimum) were evaluated as green manure and cover crops in an Ultisol soil in Viçosa, MG, Brazil. The rate of crop establishment and percent of soil coverage were evaluated. Fresh and dry biomass, root density and nutrient content were determined at flowering stage for each species. Jackbean was the best species for both rate of crop establishment and percent of ground coverage. Pigeonpea was the best in terms of root penetration in the soil, biomass production and nutrient immobilization. The crotalarias and cowpea were the most sensitive to soil compaction, having their root mass concentrated at the soil surface.